ASPEK HUKUM PERAN SERTA MASYARAKAT DALAM PELESTARIAN CAGAR BUDAYA - Fajar Winarni (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThis research, which has a title “Legal Aspect Of Community Participation In Preservation Of  Cultural Heritage (Study on Cultural Heritage School by Cultural Heritage Preservation Office Special Province of Yogyakarta)”, is to examine the implementation of Cultural Heritage School by Cultural Heritage Preservation Office Special Province of Yogyakarta as a form of community participation in preservation for cultural heritage, and to study the setting of School of Cultural Heritage in the future in order to instill public awareness of the preservation of cultural heritage.This research is an empirical law study. The research material was obtained by field research to obtain primary data and library research to obtain secondary data. Data analysis method used is descriptive qualitative.The results of this research are: First, the School of Cultural Heritage is a new program launched in 2017. The implementation of the activities is intended as an effort of socialization for the community, especially the younger generation, which is packed in the form of cultural heritage learning at school or in the office of Cultural Heritage Preservation Office Special Province of Yogyakarta and the cultural heritage site. Second, the setting of School of Cultural Heritage based on community participation and sustainable is to make the School of Cultural Heritage as a local content in the primary and secondary school curriculum. The need for this activity is set forth in the form of Governor Regulation on Local Content of Cultural Heritage and Governor Regulation concerning School of Cultural Heritage.IntisariPenelitian dengan judul “Aspek Hukum Peran Serta Masyarakat Dalam Pelestarian Cagar Budaya (Studi Terhadap Sekolah Cagar Budaya Balai Pelestarian Cagar Budaya Provinsi Daerah Istimewa Yogyakarta” ini bertujuan untuk mengkaji pelaksanaan Sekolah Cagar Budaya oleh BPCB DIY sebagai salah satu bentuk peran serta masyarakat dalam pelestarian cagar budaya dan untuk mengkaji pengaturan Sekolah Cagar Budaya oleh BPCB DIY di masa yang akan datang dalam tujuannya untuk menanamkan kepedulian masyarakat terhadap pelestarian cagar budaya.Penelitian ini merupakan penelitian hukum empiris. Bahan penelitian didapat dengan penelitian lapangan untuk memperoleh data primer dan penelitian kepustakaan untuk memperoleh data sekunder. Metode analisis data yang digunakan adalah deskriptif kualitatif.Hasil penelitian ini adalah: Pertama, Sekolah Cagar Budaya merupakan program baru yang diluncurkan pada tahun 2017. Pelaksanaan kegiatan dimaksudkan sebagai upaya sosialisasi bagi masyarakat terutama generasi muda, yang dikemas dalam bentuk pembelajaran cagar budaya di sekolah atau di kantor BPCB DIY dan di situs cagar budaya. Kedua, pengaturan Sekolah Cagar Budaya berbasis partisipasi masyarakat dan berkelanjutan adalah menjadikan Sekolah Cagar Budaya sebagai muatan lokal dalam kurikulum sekolah dasar dan menengah. Perlunya kegiatan ini dituangkan dalam bentuk Peraturan Gubernur tentang Muatan Lokal Cagar Budaya dan Peraturan Gubernur tentang Sekolah Cagar Budaya.